An optimizing communication channels, message relevance for anti-online gambling campaigns: The critical role of public awareness as a mediator - Lesmana, Hendra; Margono, Hery; Amir, Ja'far (International Journal of Applied Finance and Business Studies, 2025)
This quantitative study investigates the factors influencing the efficacy of anti-online gambling campaigns, employing a survey of 255 respondents. Using structural equation modeling, we examined the relationships between message relevance, communication channels, government regulations, public awareness, and the decrease in online gambling application users. Findings indicate that message relevance directly impacts both public awareness and a reduction in application usage. Notably, communication channels and government regulations affect application usage exclusively through their influence on public awareness, which fully mediates these relationships. Public awareness also partially mediates the impact of message relevance on application usage. These results highlight the critical role of relevant messaging in directly altering user behavior. Furthermore, the study underscores the importance of strategically utilizing communication channels and government regulations to enhance public awareness, which serves as a crucial intermediary for reducing online gambling application usage. This research offers robust managerial implications for designing effective anti-online gambling campaigns, emphasizing tailored messaging and strategic public awareness initiatives.